2012
DOI: 10.1016/j.micres.2011.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and identification of lactic acid bacteria from Tarag in Eastern Inner Mongolia of China by 16S rRNA sequences and DGGE analysis

Abstract: Tarag is a characteristic fermented dairy product with rich microflora (especially lactic acid bacteria), developed by the people of Mongolian nationality in Inner Mongolia of China and Mongolia throughout history. One hundred and ninety-eight samples of Tarag were collected from scattered households in Eastern Inner Mongolia, and total of 790 isolates of lactic acid bacteria (LAB) were isolated by traditional pure culture method. To identify these isolates and analyze their biodiversity, 16S rRNA gene sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 89 publications
(60 citation statements)
references
References 20 publications
2
56
0
2
Order By: Relevance
“…All isolates tolerated 2, 4 and 6.5% of NaCl concentration and was catalase negative. Karimi et al (2012) and Liu et al (2012) who isolated L. acidophilus from cheese and found that L.l actis and L. casei were considered as the predominated species in fermented dairy products (Tables 1 and 2). …”
Section: Physiological and Biochemical Identificationmentioning
confidence: 99%
“…All isolates tolerated 2, 4 and 6.5% of NaCl concentration and was catalase negative. Karimi et al (2012) and Liu et al (2012) who isolated L. acidophilus from cheese and found that L.l actis and L. casei were considered as the predominated species in fermented dairy products (Tables 1 and 2). …”
Section: Physiological and Biochemical Identificationmentioning
confidence: 99%
“…To avoid the inherent disadvantages of culture methods, such as underestimation of the viable cell counts, culture-independent methods, such as clone libraries or denaturing gradient gel electrophoresis (DGGE), are often used. Although there have been a few studies [11, 12] on the bacterial diversity of Airag and Tarag using the DGGE approach, too few culture-independent approaches have been performed to clarify the microbial diversity of these targets. The 16S rRNA gene sequence-based pyrosequencing method enables a detailed, comprehensive and high-throughput analysis of microbial ecology, and this method has been applied to various traditional fermented food research studies [13,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…The PCR procedure was performed as reported previously26. After the amplification, the PCR products (about 1,500 bp) were sequenced at the Shanghai Majorbio Corporation.…”
Section: Methodsmentioning
confidence: 99%